Coal Dust and Acute Respiratory Infections in South Kalimantan PT ‘X’ Coal Mining Workers. - Zikri Fathur Rahman1, Shinta Arta Mulia1, Ahmad Muslih Bambang Sugiharta1, Lili Susanti1, Abdul Rohi (Institute of Medico-legal Publications Pvt Ltd, 2020)
Occupational illness is a disease caused by a person’s work or work environment. This disease is caused by the actions of someone who is unsafe (unsafe act) and unsafe condition (unsafe condition) in carrying out his work activities. The unsafe act is an act of someone who deviates from the rules of security standards that have been set in doing work. While unsafe conditions are conditions that can endanger workers. Acute respiratory infection is an acute inflammation of the upper and lower respiratory tract caused by infection with microorganisms, bacteria, viruses, and rickets, without or accompanied by pulmonary parenchyma. Factors that affect a person affected by ARI are environmental factors, individual characteristics, and worker behavior. Environmental factors include air pollution (air pollution due to industrial output and smoke from burning fuel). Dust particles that can cause acute respiratory problems from industrial products that pollute the air such as coal dust, cement, cotton, asbestos, chemicals, toxic gases, dust in rice mills (organic dust).